Suppression of piracy armed robbery against ships and maritime terrorism: global and regional perspectives - Ahmad, Muhamad Hassan; Ansari, Abdul Haseeb; Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib (IIUM Press, International Islamic University Malaysia, 2017)
Safety of maritime navigation has been one of the major issues in the global arena for centuries. Despite the fact that piracy is one of the oldest international crimes. it recurs and seriously threatens the safety of international maritime navigation in present days. The suppression of maritime crimes should be regulated and implemented at both international and regional levels. In this book. entitled Suppression of Piracy, Armed Robbery Against Ships and Maritime Terrorism: Global and Regional Perspectives. The authors endeavour a rigorous effort to identify. examine and analyse the deficiencies or contemporary international law of the sea conventions. regional agreements and arrangements pertaining to the suppression of piracy. armed robbery against ships and maritime terrorism. The book offers numerous valuable suggestions for the improvements of the existing laws not only in ensuring the safety of maritime navigation all around the world but also in maintaining international peace and security. Policy makers, researchers. practitioners and students of international law, especially in the field of maritime security and national security. would certainly find this book as a useful guide. Readers would get insightful ideas on the suppression of piracy. armed robbery against ships and maritime terrorism without having to refer to several sources.